2022
DOI: 10.1186/s12879-022-07380-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of attitudes regarding uptake of COVID-19 vaccines among vaccine hesitant adults in the UK: a qualitative analysis

Abstract: Background The aim of this work was to explore barriers and facilitators to uptake of COVID-19 vaccines and to explore views and reactions to efforts to improve vaccine uptake among vaccine hesitant individuals. Methods Semi-structured interviews were conducted with people between the age of 18–29 years who had not had a COVID-19 vaccine, and those between 30 and 49 years who had not had a second dose of a COVID-19 vaccine. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…IMID patient organisations were identified as a useful and trusted source of information in participants' decision-making process for vaccination in our study, which is consistent with recent survey [31]. Patients actively avoided taking vaccine information from social media, contrary to vaccine-hesitant individuals in the general public [23,33]. This highlights that different types of media may be viewed differently by IMID-patients when making vaccination decisions, which may be due to the IMID-specific considerations they have and the availability of IMID-specific information from patient charities.…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…IMID patient organisations were identified as a useful and trusted source of information in participants' decision-making process for vaccination in our study, which is consistent with recent survey [31]. Patients actively avoided taking vaccine information from social media, contrary to vaccine-hesitant individuals in the general public [23,33]. This highlights that different types of media may be viewed differently by IMID-patients when making vaccination decisions, which may be due to the IMID-specific considerations they have and the availability of IMID-specific information from patient charities.…”
Section: Plos Onesupporting
confidence: 88%
“…Our findings align with the SAGE working group vaccine hesitancy matrix and a previous qualitative research study on vaccine hesitancy about vaccination against pneumococcal and seasonal flu vaccination in people with RA [21], with barriers and facilitators spanning contextual, individual/ group and vaccine/vaccination specific influences. Similar to other studies qualitatively exploring vaccine hesitancy in select population groups [22,23], we identified additional factors influencing the decision to be vaccinated that were specific to this patient group, such as concerns of vaccination inducing IMID-flare, as well as those specific to the COVID-19 pandemic, such as vaccination as an opportunity to end social restrictions. We also demonstrated how some barriers and facilitators differ from one vaccine to another.…”
Section: Discussionmentioning
confidence: 80%
“…Uptake of primary series (i.e., both doses) of COVID-19 vaccines in the UK reached 93.3% uptake of a first dose and 87.5% second doses by July 2022. 10 Many chose to vaccinate to protect personal and community health and alleviate living with COVID-19 public health measures; 11 however, variations in uptake were persistent and aligned with factors associated with intention to vaccinate against COVID-19. The COVID-19 Social Study found 36% of adults in the UK were vaccine hesitant, with low socio-economic status, being female, belonging to an ethnicity minority group, and not vaccinating against influenza during the previous influenza season identified as factors affecting receipt of COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the pandemic, how people perceive the threat posed by COVID-19 has been shown to vary based on a number of factors such as age [5], political ideology [6,7], and philosophical beliefs [8]. How people perceive the risk of COVID-19 matters as those who do not identify COVID-19 to be a serious threat are likely to undervalue the benefits of vaccination [4] and are therefore less likely to choose to receive a vaccine [9][10][11][12]. Furthermore, people who do not consider COVID-19 to present a serious threat may also be reluctant to receive a vaccine because they are more likely to believe that they are more at risk from potential harms from vaccination than from acquiring COVID-19 [4,9,10].…”
Section: Introductionmentioning
confidence: 99%